2018
DOI: 10.1177/0142331217751040
|View full text |Cite
|
Sign up to set email alerts
|

Model-free tuning strategy of fractional-order PI controller for speed regulation of permanent magnet synchronous motor

Abstract: This paper investigates a model-free tuning method of a fractional-order proportional–integral (FOPI) controller and its application for the speed regulation of a permanent magnet synchronous motor (PMSM). Firstly, the presented practical FOPI tuning method formulates the FOPI controller parameter identification problem via virtual reference feedback tuning (VRFT). Under the lack of accurate models, the proposed model-free method depends only on the measured input–output data of the closed-loop PMSM servo syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…However, obtaining a reliable model of a system from the first principle or using system identification tools, is a quite difficult and time-consuming task, especially for modern complex systems. For this reason, several techniques were developed for model-free or data-driven control design including model-free adaptive control (MFAC) [24], virtual reference feedback tuning (VRFT) [25], and iterative feedback tuning (IFT) [26]. In VRFT and IFT techniques, the controller structure is identified first and the input-output data are used to tune the control parameters offline.…”
Section: Introductionmentioning
confidence: 99%
“…However, obtaining a reliable model of a system from the first principle or using system identification tools, is a quite difficult and time-consuming task, especially for modern complex systems. For this reason, several techniques were developed for model-free or data-driven control design including model-free adaptive control (MFAC) [24], virtual reference feedback tuning (VRFT) [25], and iterative feedback tuning (IFT) [26]. In VRFT and IFT techniques, the controller structure is identified first and the input-output data are used to tune the control parameters offline.…”
Section: Introductionmentioning
confidence: 99%
“…The experiments showed that fractional order controllers provided superior control characteristics compared to conventional PID. Xie et al (2018) investigated a model-free tuning method of fractional order PI controller. The controller parameter identification method depends only on the measured input-output data of the closed-loop PMSM servo system.…”
Section: Introductionmentioning
confidence: 99%
“…Electromechanical systems are prone to a broad class of disturbances and dynamic uncertainties, (Das, 2018; Kim, et al 2018; Sun, et al 2018; Xie et al, 2019; Xu et al, 2017), which in most cases are neglected depending on the operational regime. However, for precision tasks some non-smooth effects may disrupt the system performance, if they are not actively compensated through the dynamic controller, for instance, backlash (Ahangarian-Abhari et al, 2018; Li and Yang, 2019; Tenreiro-Machado, 2013), dynamic friction effects (Huang and Chiu, 2009), and not necessarily integer-order differentiable disturbances due to input noise and mechanical vibrations (Loutridis and Trochidis, 2004).…”
Section: Introductionmentioning
confidence: 99%